Wordwall, Media Pembelajaran, Pe Penerapan Wordwall Sebagai Media Pembelajaran Interaktif dalam Meningkatkan Pemahaman Peserta Didik Kelas XI E SMA Negeri 1 Kupang - Nesimnasi, Ance Delwanti; Robot , Marselus; Christina , Frederika (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
ABSTRACT The purpose of carying out this research is to evaluate the increase in participants' understanding in class XI E of SMA Negeri 1 Kupang by using Wordwall as an interactive learning medium. This classroom action research consists of two cycles which include four main stages: planning, implementation, observation, and reflection. The findings of this research are as follows: a) In cycle I, the use of the Wordwall application shows that the majority of students have not reached the standard of completeness in learning. The average learning outcome value reaches 75% with a classical completion level of 60%. b) In cycle II, there was an increase in student activity where 33 students showed active participation in the learning process with an average score of 90%, which was categorized as a very good classical level. In addition, 33 other students achieved average scores of 85% and 90%. In answering questions on Wordwall, students also showed a good level of activeness with an average score of 75%, involving 28 students. Thus, the implementation of Wordwall is able to increase students' interest in learning, especially in understanding scientific work material in Class XI E of SMA Negeri 1 Kupang Keywords: Wordwall, Learning Media, Increasing Understanding, Classroom Action Research